Tingkat Keterampilan Dribbling, Shooting Dan Passing Kontrol Bola Futsal Pada Peserta Ekstrakurikuler Futsal Laki – Laki Di Smp Negeri 18 Bengkulu Selatan - Ilham Rachmat Ramadhan; Dolly Apriansyah; Azizatul Banat (Educative Sportive, 2026)
This study aims to determine the level of futsal ball control dribbling, shooting and passing skills in male futsal extracurricular participants at SMP Negeri 18 Bengkulu Selatan. This type of research is quantitative descriptive research with a sample of 22 students. The results of the study conducted on 22 futsal players at SMP Negeri 18 Bengkulu Selatan, it can be concluded that their futsal dribbling skill level is in the moderate category in general. This evaluation provides an adequate picture of the condition of dribbling skills which is an important foundation in developing their futsal abilities. The results of this study reinforce the importance of continuous efforts to improve the quality of futsal training in junior high schools, including the development of more effective strategies for teaching and training dribbling skills. Shooting skills of futsal players of SMP Negeri 18 Bengkulu Selatan are in the poor category with the results obtained in the category of "very poor" as many as 1 person with a presentation of 5%, the category of "less" as many as 15 people with a percentage of 68%, the category of "moderate" as many as 4 people with a percentage of 18%, and the category of "good" as many as 2 people with a percentage of 9% and in the category of very good as many as 0 people with a percentage of 0%. The Passing Control skill test of futsal players of SMP Negeri 18 Bengkulu Selatan is in the Good category with the results obtained in the category of "very poor" as many as 0 people with a percentage of 0%, then in the category of "less" as many as 6 people with a percentage of 27%, the category of "moderate" as many as 3 people with a percentage of 14%, and the category of "good" as many as 13 people with a percentage of 59% and in the category of very good there are none.